The effects of migration and remittances on inequality in rural Pakistan - Adams, Richard H., Jr. (Pakistan Institute of Development Economics, 1992)
In the Third World remittances - defmed as money and goods that are transmitted by migrant workers to their households back home - can have a profound impact upon rural income distribution. This is true for both internal remittances, which are often small but widespread among the rural population, as well as for international remittances, which are typically larger and more concentrated. Despite these considerations, there is still no general consensus about the effect of internal or international remittances on rural income distribution in the Third World. On the one hand, Lipton (1980) argues that in India internal remittances worsen rural inequality because they are earned mainly by upper-income villagers. With respect to international remittances, Gilani, Khan and Iqbal (1981) in Pakistan and Adams in Egypt (1991, 1989) produce similar fmdings. On the other hand, some empirical studies suggest a very different outcome. For example, Stark, Taylor and Yitzhaki (1986) fmd that internal and international remittances in Mexico have an egalitarian effect on rural income distribution.1 Two major reasons appear to account for such lack of consensus on the effect of remittances upon rural income distribution: the use of local-level data collection techniques that preclude making unambiguous empirical judgements about the effects of remittances; and the reluctance or inability to use predicted income functions to accurately estimate income before and after remittances.